Molecular dynamics simulations of the interactions of potential foulant molecules and a reverse osmosis membrane - Hughes, Zak; Gale, Julian (The Royal Society of Chemistry, 2011)
Reverse osmosis (RO) is increasingly one of the most common technologies for desalination worldwide. However, fouling of the membranes used in the RO process remains one of the main challenges. In order to better understand the molecular basis of fouling the interactions of a fully atomistic model of a polyamide membrane with three different foulant molecules, oxygen gas, glucose and phenol, are investigated using molecular dynamics simulations. In addition to unbiased simulations, umbrella sampling methods have been used to calculate the free energy profiles of the membrane-foulant interactions. The results show that each of the three foulants interacts with the membrane in a different manner.It is found that a build up of the two organic foulants, glucose and phenol, occurs at the membrane-saline solution, due to the favourable nature of the interaction in this region, and that the presence of these foulants reduces the rate of flow of water molecules over the membrane-solution interface. However, analysis of the hydrogen bonding shows that the origin of attraction of the foulant for the membrane differs. In the case of oxygen gas the simulations show that a build up of gas within the membrane is likely, although, no deterioration in the membrane performance was observed.